2000
DOI: 10.1111/j.1745-6584.2000.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Haloacetic Acids and Trihalomethanes in an Aquifer Storage and Recovery Program, Las Vegas, Nevada

Abstract: The fate of disinfection byproducts during aquifer storage and recovery (ASR) is evaluated for aquifers in southern Nevada. Rapid declines of haloacetic acid (HAA) concentrations during ASR, with associated little change in Cl concentration, indicate that (HAAs) decline primarily by in situ microbial oxidation. Dilution is only a minor contributor to HAA concentration declines during ASR. Trihalomethane (THM) concentrations generally increased during storage of artificial recharge (AR) water and then declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Singer et al (1999) reported HAA removal by GAC filtration and suggested that biological degradation of HAAs had occurred in GAC filters. Thomas et al (2000) evaluated the fate of HAAs during aquifer storage and recovery in southern Nevada. A rapid decline of HAA concentrations during aquifer storage and recovery indicated in situ microbial oxidation of HAAs.…”
mentioning
confidence: 99%
“…Singer et al (1999) reported HAA removal by GAC filtration and suggested that biological degradation of HAAs had occurred in GAC filters. Thomas et al (2000) evaluated the fate of HAAs during aquifer storage and recovery in southern Nevada. A rapid decline of HAA concentrations during aquifer storage and recovery indicated in situ microbial oxidation of HAAs.…”
mentioning
confidence: 99%
“…Studies conducted on DBP transformation in soil matrix concluded that bioconversion and dilution are the two mechanisms by which HAA5 get transformed or decline in their concentrations during transport in the soil system (Singer et al, 1993;Miller et al, 1993;Bernholtz et al, 1994;Pyne et al, 1996;Thomas et al, 2000;Landmeyer et al, 2000). All these studies except Landmeyer et al, 2000, were conducted to evaluate the fate of disinfection byproducts during aquifer storage and recovery (ASR) in aquifers of Las Vegas Valley, Nevada.…”
Section: Fate Of Dbps In Laurel Pondmentioning
confidence: 96%
“…In recent studies by Thomas et al (2000) and Landmeyer et al (2000), results of both field and laboratory studies using geochemical modeling and monitoring showed that HAA5 reduction is primarily by in situ microbial oxidation, while TTHM reduction is by biodegradation, volatilization, and dilution. In their studies, rapid decline of HAA5 concentrations with little associated change in chlorine concentration indicted that dilution is not the major process for reduction in HAA5 concentration.…”
Section: Fate Of Dbps In Laurel Pondmentioning
confidence: 98%
“…Although not addressed in this paper, geochemical processes are important factors in the success of an ASR system. Geochemical studies of ASR systems include investigations of disinfection by‐products produced by reactions between the injected chlorinated water and naturally occurring organic compounds (e.g., Thomas et al 2000; Fram et al 2003). Of primary interest are the mechanism and time period at which these disinfection by‐products degrade in the aquifer.…”
Section: Introductionmentioning
confidence: 99%